Development of Local Functional Food Made of Buffalo Milk Improved with Culture Probiotics (Lactobacillus casei) - Djoko Kisworo (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
Abstract The research was conducted to develop functional food products of milk-based livestock origin (Semi hard-type cheese), with the addition of pure culture Lactobacillus casei as a probiotic agent, and citric acid and Mucor meihei as milk coagulants. The research material was semi-hard type cheese made of approximately 35 liters of buffalo milk from West Sumbawa Regency as a basic ingredient with the probiotic pure culture. The results showed that the pure culture of probiotic (Lactobacillus casei) at levels of 10% and 15% can survive and develop quite well in semi-hard cheese during aging, from 1 day, 7 days, and 14 days, respectively (3.79 – 5.92) and (4.91 – 6.31) log cfu g-1. While the 0.025% rennet of the volume of milk from Mucor miehei gives a pretty good result, it can be seen from the product recovery which can reach (34.30 + 0.32) %. During aging for 14 days, an organoleptic quality which includes aroma, color, and texture was getting better, with the criteria of a semi-hard aroma, yellowish-white color, and semi-hard texture. It can be concluded, that semi-hard type cheese can be used as one of the functional foods of probiotic carriers. To get the therapeutic effect, this probiotic should be consumed at least 100 grams per serving.